Acute caffeine supplementation improves jumping, sprinting, and change-of-direction performance in basketball players when ingested in the morning but not evening - Stojanovic, E.; Scanlan, A. T.; Milanovic, Z.; Fox, J. L.; Stankovic, R.; Dalbo, V. J. (European Journal of Sport Science, 2022)
This study compared the effects of acute caffeine supplementation (3 mg/kg) administered in the morning and evening on performance-related variables in basketball players. Eleven, national-level, adolescent male basketball players underwent field-based fitness testing on four occasions: morning (10:00) with caffeine ingestion (AMCAFF), morning (10:00) with placebo ingestion (AMPLAC), evening (21:00) with caffeine ingestion (PMCAFF), and evening (21:00) with placebo ingestion (PMPLAC). Fitness testing included of a countermovement jump without arm swing (CMJ), CMJ with arm swing (CMJAS), squat jump (SJ), Lane Agility Drill (LAD), 20-m linear sprint, and Suicide Run with (SRD) and without dribbling (SR). Data were analyzed using two-way repeated measures analyses of variance and paired t-tests, with effect sizes (ES) also determined for all pairwise comparisons. Follow-up t-test comparisons revealed that AMCAFF produced small-moderate, significant (p<0.001), improvements in CMJ (ES = 0.51), CMJAS (ES = 0.40), SJ (ES = 0.51), and SR (ES = -0.45) compared to AMPLAC. AMCAFF also produced a moderate, significantly (p<0.001) faster LAD (ES = -0.61) compared to PMCAFF. PMPLAC demonstrated small-moderate, significant (p<0.05) improvements in CMJ (ES = 0.43), CMJAS (ES = 0.48), and 20-m sprint (ES = -0.63) compared to AMPLAC. In contrast, AMPLAC resulted in large, significantly (p<0.001), faster SRD (ES = -1.46) and SR (ES = -1.59) compared to PMPLAC. Given the ergogenic effects of caffeine during basketball-specific fitness tests appear to be influenced by time of ingestion, basketball practitioners should consider administering caffeine only to players in the morning to improve vertical jump, sprinting, and change-of-direction performance, with no beneficial effects observed with caffeine ingestion in the evening.